2009
DOI: 10.1159/000209289
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatments with Pimecrolimus, Tacrolimus and Medium- to High-Potency Corticosteroids, and Risk of Lymphoma

Abstract: Background/Aims: A potential risk of lymphoma associated with the use of topical calcineurin inhibitors is debated. We assessed the risk of lymphoma among patients treated with topical pimecrolimus, tacrolimus or corticosteroids. Methods: We conducted a cohort study using health insurance claims data. Cohorts of initiators of topical pimecrolimus, tacrolimus and corticosteroids, along with cohorts of persons with untreated dermatitis and randomly sampled enrollees were identified from January 2002 to June 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 26 publications
4
79
0
2
Order By: Relevance
“…10 However, many large-scale analyses have indicated that topical tacrolimus does not increase the risk of malignant lymphoma. [11][12][13][14][15] In addition, topical tacrolimus was effective for the treatment of cutaneous T-cell lymphoma in one case 16 and in the treatment of cutaneous lesions of angioimmunoblastic T-cell lymphoma in another case. 17 These cases are of great interest in terms of the relationship between tacrolimus and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, many large-scale analyses have indicated that topical tacrolimus does not increase the risk of malignant lymphoma. [11][12][13][14][15] In addition, topical tacrolimus was effective for the treatment of cutaneous T-cell lymphoma in one case 16 and in the treatment of cutaneous lesions of angioimmunoblastic T-cell lymphoma in another case. 17 These cases are of great interest in terms of the relationship between tacrolimus and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of TCL associated with use of pimecrolimus cream was insignificantly increased (RR 2.32, 95% CI, 0.89 -6.07) (23,43). A cohort study by Schneeweiss et al reported no significant association between lymphoma and both TCIs (tacrolimus; RR 1.36, 95% CI, 0.47 -3.98, pimecrolimus: RR 1.63, 95% CI, 0.75 -3.54) (24). In case control studies, the risk for developing lymphoma was even more insignificant (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…Many opinion leaders and medical associations, including the American academy of allergy, asthma and immunology (AAAAI), American college of allergy, asthma and immunology (ACAAI), American academy of dermatology, canadian dermatology association (CDA), and Canadian society of allergy and clinical immunology (CSACI) released position statements, expressing disagreement about box warning, promoting the safety of the TCIs and demanding reconsideration of the alert (15)(16)(17)(18). In September 2010, the FDA released a comprehensive review of TCI safety summarizing data from six studies including more than 6 million patients (19)(20)(21)(22)(23)(24)(25)(26). Later on, in May, 2011 according to a total of 72 cases of malignancy that had been reported in children treated with TCI, the FDA issued an addendum (27,28).…”
Section: The Us Fda "Black Box" Warning For Tcis and Fda Comprehensivmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4) In contrast, other studies revealed no significant differences between TL use and non-use with regard to an increased risk of lymphoma. 5,6) Due to short durations and potential study biases in these reports, results have been controversial. Thus, the FDA has advised that monitoring for occurrence of TL-related cancer be continued.…”
mentioning
confidence: 99%